Strain induced martensite formation characteristics of austenite stainless steel during various loading conditions. (March 2014) - Okayasu, M.; Fukui, H.; Ohfuji, H.; Shiraishi, T.
<x content-type="archive" xml:space="preserve">Abstract</x> The strain induced martensitic transformation (SMT) of the austenite stainless steel (SUS 304) under cyclic loading and static loading was investigated directly using electron backscattered diffraction. Two different SMT characteristics are observed, which are attributed to the differences of plastic and twinning deformation. The maximum cyclic stress has a strong influence on the SMT. The total area fraction of the Fe-α′ phase increases significantly when the maximum cyclic load is >80% σUTS. In other words, the SMT is apparently absent when the samples are loaded with less than σmax = 70% σUTS, although such samples are fractured completely. Moreover, there is a clear R ratio effect on the SMT. For example, the loading condition R = −1 gives rise to a strong SMT compared to R = 0·1 due to the more severe strain caused by the compressive stress. In contrast, no clear frequency effect (1 versus 30 Hz) on the SMT is detected, which may be attributed to the same maximum cyclic stress. Like the SMT characteristics under cyclic loading, the proportion of Fe-α′ phase shows no clear increase until the sample is loaded statically to a tensile stress <70% σUTS.